Multidisciplinary Perspectives of Clinical Trials in Theranostics - Pathmaraj, Kunthi; Lee, Sze Ting (World Journal of Nuclear Medicine, 2025)
Theranostics and clinical trials are driving the future of nuclear medicine and require a multidisciplinary approach to achieve the best possible care for the patient. Theranostics refers to using chemical compounds with similar diagnostic and radiotherapeutic applications. Therefore, the biodistribution remains the same for the imaging and therapy portions, a low radiation dose being delivered during imaging, and a higher radiation dose being delivered to the target disease areas during the treatment phase. The new era of theranostics has revolutionized nuclear medicine through the prospective phase 3 clinical trials, which have resulted in its adoption into the treatment paradigms of patients, particularly those with neuroendocrine tumors and prostate cancer. Molecular imaging can be used to assess the role and utility of new tracers and molecular endpoints to help improve the understanding of tumor biology and evaluation of treatment response, leading to intelligent clinical trial design and more rapid drug development. Clinical trials networks such as EANM Research Ltd. (EARL), SNMMI Clinical Trials Network (CTN), and Australasian Radiopharmaceutical Trials Network (ARTnet), encourage a standardized approach and promote a collaborative approach to clinical trials in molecular imaging. Clinical Trials in Theranostics require the skills and expertise of a multidisciplinary team including the principal investigator, nuclear medicine specialists, study coordinators, medical physicists, radiopharmaceutical scientists, nuclear medicine technologists, research nurses, and research assistants. All personnel involved in theranostics clinical trials should be certified in Good Clinical Practice (GCP). Accurate documentation and record keeping in clinical trials provides validation that clinical trials is conducted at the highest ethical and clinical standards, meets the expectation of the study protocol, and adheres to GCP. Radiation safety is a critical factor for staff, patients, and the public in theranostics and clinical trials and must follow country-specific guidelines and international guidelines to ensure basic safety standards are met. As theranostics and clinical trials continue to stamp their mark in molecular imaging and radionuclide therapy, it is imperative that nuclear medicine professionals remain upskilled and adequately trained in these two aspects of the profession to ensure optimal care is delivered to the patient.
Keywords: clinical trials; clinical trials networks; Good Clinical Practice; radiation safety; theranostics